Construction of Biocompatible Hydrogel Scaffolds With a Long-Term Drug Release for Facilitating Cartilage Repair - Zhang, Wei; Chen, Rui; Xu, Xiong; Zhu, Liang; Liu, Yanbin; Yu, XiaoJie; Tang, GuoKe (Frontiers in Pharmacology, 2022)
In tissue engineering, hydrogel scaffolds allow various cells to be cultured and grown in vitro and then implanted to repair or replace the damaged areas. Here in this work, kartogenin (KGN), an effectively chondro-inductive non-protein bioactive drug molecule, was incorporated into a composite hydrogel comprising of the positively charged chitosan (CS) and methacrylated gelatin (GelMA) polymers to fabricate appropriate microenvironments of bone marrow mesenchymal stem cells (BMSCs) for cartilage regeneration. Based on the combination of physical chain entanglements and chemical crosslinking effects, the resultant GelMA-CS@KGN composite hydrogels possessed favorable network pores and mechanical strength. In vitro cytotoxicity showed the excellent biocompatibility for facilitating the cell growth, adhesion, proliferation and differentiation. The long-term sustainable KGN release from the hydrogel scaffolds in situ promoted the chondrogenic differentiation that can be employed as an alternative candidate for cartilage tissue regeneration.